2003
DOI: 10.1016/s0022-0728(03)00141-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidative adsorption and reductive desorption of a self-assembled monolayer of decanethiol on the Au(111) surface in KOH+ethanol solution

Abstract: The electrochemical characteristics of an Au(111) electrode were investigated in 0.1 M KOH ethanol solutions containing various concentrations of decanethiol. Anodic and cathodic peaks corresponding to the oxidative adsorption and reductive desorption, respectively, of a self-assembled monolayer (SAM) of decanethiol were observed. Both peaks negatively shifted with the increase in the thiol concentration by ca. 57 mV/decade, showing that the redox process is a one-electron process. The adsorbed amount determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 44 publications
11
45
0
1
Order By: Relevance
“…[ [18,35,36,38,39]. This discrepancy may be caused by an error in the estimation of real surface area.…”
Section: Concentration Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…[ [18,35,36,38,39]. This discrepancy may be caused by an error in the estimation of real surface area.…”
Section: Concentration Dependencementioning
confidence: 99%
“…From the area, shape, and position of the cathodic peak corresponding to reductive desorption of the SAM, one can obtain much information on the SAM such as the amount adsorbed thiol molecules and stability and conformational order of the SAM. We have shown that the SAM can be formed by anodic oxidative adsorption, i.e., a reverse reaction of the reductive desorption, in an alkaline ethanolic solution containing thiol and the coverage of SAM increased and the peak position shifted negatively with adsorption time and the rates of formation and the conformational order of the SAM are higher in the decanethiol solution of higher concentration [39,40].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[52][53][54][55][56][57][58][59][60][61] Recently, we briefly reported that quantitative analysis of the reductive desorption of an electrodeposited thiolate layer provided us with useful information about the formation process of a SAM such as the time dependency of the adsorbed amount and the order of the SAM. 62 In this work, we studied in detail the anodic oxidative adsorption and cathodic reductive desorption of decanethiol layers on Au(111) electrodes in 0.1 M KOH ethanol solutions containing various concentrations of decanethiol. The effects of sweep rate and thiol concentration under the condition of continuous potential cycling as well as the effects of holding time and thiol concentration under the condition of potentiostatic oxidative SAM formation on the amount of adsorbed thiolate and the order of the SAM were evaluated from the charge and position of the reductive peak, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that alkylthiol SAMs are electrochemically desorbed from a gold surface by the following reduction process in an alkaline aqueous solution: [56][57][58][59][60][61][62][63][64][65] Au Figure 2 shows LSVs of the Au(111) electrodes modified with the TMMPP SAMs, which were prepared for various dipping periods, measured in 0.1 M KOH at a scan rate of 20 mV s ¹1 when the potential was negatively scanned from 0 to ¹1.4 V. Between ¹0.7 and ¹1.1 V, three cathodic peaks, which seemed to be due to the reductive desorption of the SAM, were observed. The two more negative peaks observed around ¹0.9 and ¹1.0 V were reported only in the case of the mercaptopyridine and mercaptopyrrole SAMs.…”
Section: Electrochemical Reductive Desorptionmentioning
confidence: 99%